Thermal stress-related physiological, behavioral, and serum biochemical responses in indigenous pigs adapted to Eastern Himalayan region - Govindasamy, Kadirvel; Gonmei, Chamniugongliu; Singh, Ningthoujam Suraj; Singh, Nakambam Manoranjan (Frontiers in Veterinary Science, 2022)
The current study was carried out to investigate the effect of micro-environmental variations on physiological, behavioral and serum biochemical parameters of indigenous (Niang Megha), Hampshire and crossbred (75% Hampshire X 25% Niang Megha). Rectal temperature (TR), skin surface temperature (TSS), respiration rate (RR) and heart rate (HR) were recorded at 0900 and 1600 hours weekly once for two months for each season in grower pigs of each genotypes. CCTV video cameras were utilized to observe the behavioral changes. Blood (5ml) were collected to estimate different biochemical parameters. Season affected (p<0.05) all physiological parameters which generally increased during summer except TR and RR of indigenous pig. The TR, TSS, RR and HR were significantly (p<0.05) higher for Hampshire than indigenous and crossbred in summer season. The frequency and behavioral activities to heat loss or to conserve heat such as shivering, wallowing were lower except for physical activity was higher at all time in indigenous pigs. Seasonal variations influenced metabolic activity and serum activity of alkaline phosphatase (ALP) and alanine transaminase (ALT), which rose in summer in all genotypes. Serum ALP and thyroxine (T4) were significantly (p<0.05) higher for indigenous pig in both the seasons. There was significantly (p<0.05) different in insulin level between seasons and during winter among the genotypes with no significant between Hampshire and crossbred in winter. However, superoxide dismutase (SOD) showed no significant different in the study. Indigenous pigs had the lowest serum cortisol concentrations, whereas Hampshire had the highest. The current study's findings on several parameters of three different genotypes suggest that indigenous pigs in this region are more adaptable to the region's changing climatic conditions.